Climatologies of Geometric and Tropospheric BrO Vertical Column Densities derived from multiple UV-Vis Satellite Remote Sensors for Polar Spring over the Arctic - Bougoudis, Ilias; Blechschmidt, Anne-Marlene; Richter, Andreas; Seo, Sora; Burrows, John Philipp (Institut für Umweltphysik, Universität Bremen, 2024)
This dataset contains long-term averages of geometric and tropospheric BrO Vertical Column Densities (VCDs), derived using the DOAS method (Platt and Stutz, 2008), for polar springs (March, April, May) over the Arctic, retrieved from four UV-VIS satellite sensors: GOME (1996-2003), SCIAMACHY (2002-2012), GOME-2A (2007-2017) and GOME-2B (2013-2017), i.e. 22 years in total. All data is available on a 0.5° x 0.5° degree grid. The underlying retrievals of BrO have been verified for consistency between the sensors. Geometric VCDs are derived from total slant columns of BrO by application of a stratospheric air mass factor. The method by Theys et al. (2011) is applied in order to derive tropospheric VCDs from retrieved total slant columns of BrO and a simple tropospheric AMF assuming a surface reflectance of 0.9 and a BrO surface layer of 400 m thickness. The data is available for every sensor separately. In addition, corresponding merged data have been derived by averaging retrievals for dates for which more than one sensor was in operation. Merged climatological monthly means for the months with sufficient light and hence coverage (March to September) are provided in addition. Finally, geometric and tropospheric annual cycles (on a daily and monthly basis) are provided for each instrument separately. We gratefully acknowledge the funding by the Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) - Projektnummer 268020496 - TRR 172, within the Transregional Collaborative Research Center "ArctiC Amplification: Climate Relevant Atmospheric and SurfaCe Processes, and Feedback Mechanisms (AC)³".
Keywords: Arctic Amplification; Halogen oxides; satellite remote sensing